Pulmonary function in relation to muscle endurance and functional capacity in children with bronchial asthma - Zahera Raafat Zedan; Walaa Abd El-Hakiem Abd El-Nabie; Shimaa AboEldahab Ahmed; Eman Mohamed Tantawy; Mai Mohamed Khalaf (BMC Pulmonary Medicine)
Abstract Background Bronchial asthma is a major global health concern among children. It poses a significant global public challenge, causing around 22.8 million years of life lost to disability and 495,100 asthma-related deaths. Objective The goal of the study was to investigate the relationship between pulmonary function in children with bronchial asthma and both the muscle endurance of the deep cervical flexors and overall functional capacity. Methods This cross-sectional study involved sixty-four pediatric patients diagnosed with bronchial asthma, aged from 8 to 10 years old from both sexes. Their body mass index was from 5th percentile to less than 85th percentile for age, gender and height. They were evaluated and diagnosed by using spirometry. Pulmonary function (vital capacity(VC), peak expiratory flow (PEF), forced expiratory volume in 1s (FEV1), forced expiratory volume in 1s / forced vital capacity (FEV1/FVC), muscle endurance, and functional capacity were assessed by using spirometry, pressure biofeedback, and 6-minutewalk test respectively. Results The findings indicated a clear and significant positive association between pulmonary function measures, including (VC, PEF, FEV1 and the FEV1/FVC ratio), with both the cervical flexion test and the six-minute walk test (6MWT). These correlations were statistically significant, with p-values of ≤ 0.05. Conclusion Pulmonary function is associated with endurance of cervical flexors and functional capacity in pediatric patients with bronchial asthma.